2007
DOI: 10.1038/sj.jp.7211896
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a ‘Hypothermia for HIE’ program: 2-year experience in a single NICU

Abstract: Hypothermia has been shown to be neuroprotective in some newborns with moderate-to-severe perinatal hypoxic-ischemic encephalopathy (HIE). In 2006, the American Academy of Pediatrics recommended that institutions that choose to use therapeutic hypothermia do so in the context of a rigorous protocol, with systematic collection of patient data including neurodevelopmental follow-up. In this report, we describe our experience with implementation of a 'Hypothermia for HIE' program in a single tertiary care Neonata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 18 publications
0
23
1
2
Order By: Relevance
“…To date, induced hypothermia by either selective head or whole body cooling within 6 hours of birth 1-3 is the only effective treatment for HIE shown to decrease the combined outcome of death or severe neurodisability at 18 months. 4-10 Several randomized clinical trials 5,7,9 and other single-institution studies [11][12][13][14][15][16] have included protocols that have initiated and/or continued cooling therapy during interfacility transport of "outborn" neonates delivered far from a cooling center or referred several hours after delivery. Although these studies have shown that cooling on transport is feasible and provide guidelines for protocol development, 17 efficacy and safety concerns such as potential overcooling 13 remain in question.…”
Section: Introductionmentioning
confidence: 99%
“…To date, induced hypothermia by either selective head or whole body cooling within 6 hours of birth 1-3 is the only effective treatment for HIE shown to decrease the combined outcome of death or severe neurodisability at 18 months. 4-10 Several randomized clinical trials 5,7,9 and other single-institution studies [11][12][13][14][15][16] have included protocols that have initiated and/or continued cooling therapy during interfacility transport of "outborn" neonates delivered far from a cooling center or referred several hours after delivery. Although these studies have shown that cooling on transport is feasible and provide guidelines for protocol development, 17 efficacy and safety concerns such as potential overcooling 13 remain in question.…”
Section: Introductionmentioning
confidence: 99%
“…If cooling is delayed until the arrival of an infant at a cooling centre, this is likely to reduce its efficacy. A number of passive cooling12 13 and combined passive and active cooling14 15 strategies have been used during transport. In the largest series of babies undergoing passive cooling, a significant proportion of infants were overcooled,13 suggesting the need for clear and validated passive cooling protocols.…”
Section: Introductionmentioning
confidence: 99%
“…Aunque existen recomendaciones y programas específi-camente en el tratamiento con hipotermia 5,[16][17][18][19] , no resulta fácil encontrar protocolos o vías clínicas que ordenen todo el proceso asistencial del RN en riesgo de presentar EHI antes del inicio de la hipotermia terapéutica 10,20 . Si en la práctica clínica el tratamiento con hipotermia exige rigor para optimizar su éxito fuera de ensayos clínicos 21 , este rigor también es necesario en la vigilancia previa y en la selección adecuada de los candidatos a recibir dicho tratamiento 10,22 .…”
Section: Discussionunclassified
“…En nuestro país, comunidades como Madrid o Cataluña disponen de equipos entrenados y con protocolos de manejo del RN con EHI durante el transporte. El programa ARAHIP, a través de la vigilancia sistemática de todo RN con riesgo de EHI y la aplicación de recomendaciones protocolizadas para el traslado, ha permitido una alta tasa de tratamiento con hipotermia en el periodo ventana, iniciándose en el hospital emisor y manteniéndose durante el traslado 17,18 . La excelente comunicación entre los centros emisores y receptores, con apoyo a los equipos de transporte, ha sido clave para estos resultados.…”
Section: Discussionunclassified